The people in question : citizens and constitutions in uncertain times - Shaw, Jo (Bristol University Press, 2020)
Questions of citizenship and the role of constitutions in determining its boundaries are under scrutiny in this judicious and accessible analysis from Jo Shaw. With populism on the rise and debates about immigration intensifying, it draws on examples from around the world to set out the shifting boundaries of state inclusion and exclusion.